UJI BSLT DAN ANTI OKSIDAN EKSTRAK N-BUTANOL DAN AIR PADA RANTING TANAMAN SIRIH HUTAN (Piper aduncum .L.) - Syelvia Lousiana Ningsih Kalauw; Yerwanto Ilang; Rudi Kartika; Fauzi Rachman; Partomouan Simanjuntak (PROSIDING SEMINAR KIMIA, 2014)
Forest betel plant is a plant belonging to the Piperaceae tribe. Sap of plants are often used by people as a cure boils and leaves as toxicity to mosquito larvae o f Aedes aegypti L. Was tested for BSLT (Brine shrimp Lethality Test) and antioxidants in ethanol and water ext ract of the twigs of the plant betel leaves this forest, the concentration used in the test BSLT 10 , 100 and 1000 pp m and antio xidant tests with obstacle (inhibit ion)% 5, 10, 25, 50 and 100pp m. Principles used in to xicity tests of ethanol and water extracts of p lant twigs forest betel Piper aduncum .L ( family :p iperaceae) BSLT (Brine shrimp Lethality Test) determined by the method of total mortality of larvae shrimp Artemia salina Leach extract co mpounds due to the influence of natural materials with a part icular concentration and antioxidant principle is based on the color of the solution changes DPPH (1,1-di fenil-2-pikrilhidrasil) from purple to yellow due to the presence of antio xidant compounds. Where the results of research in BSLT test showed that the LC 50 value twigs of 33.88 pp m ethanol extract and water extract of 323.593 ppm. The antio xidant test IC 50 values obtained at 140.732 pp m ethanol extract and water ext ract of 438.687 pp m with a b lank absorbance by 0.813.